COVARIUM 10 A NEW MEDICINE AGAINST INTESTINAL AMOEBIASIS FROM CODIAEUM VARIEAGATUM (EUPHORBIACEAE) - Melanie, K.; Bilong, N.; Moundipa, P. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
During a survey within the Bamum tribe reputed for their attachment to their traditional way of life, 52 medicinal plants were selected for their use to treat liver and intestinal disorders. Among the 52 plants C. variegatum displayed high amoebicidal activity in vitro in polyxenic culture. We then focussed on developing an improved traditional drug. Extract prepared as described traditionally displayed excellent in vitro activity against trophozoites of Entamoeba histolytica and the activity was even higher compared to that of the reference drug metronidazole (3.15 Âµg/ml and 5.97 Âµg/ml respectively). A finger print of the therapeutic extract revealed the presence of flavonoids; coumarins, and polyphenols compounds. Toxicity studies on mice and rats did not reveal any mortality at acute dose of 5 g/kg and no alteration of the in vivo marker liver and kidney functions (aminotransferases, creatinine, mixed function oxidase enzymes). Leaves of the plants ware harvested and processed according to traditional advice to manufacture a herbal tea bag called Covarium 10. This drug was used for phase I clinical trial after the approval of the Cameroonean Ethical Committee. Two to three days were sufficient to completely clear the parasite from the intestine following the administration of one tea bag per day, with no secondary clinical effect observed. Biochemical analysis of the blood showed no changes in patients. The results are being patented. Acknowledgement: Yaounde Hospital, Institute of Tropical Medicine in Hambourg, IFS.